Occupational Therapy and Prevention of Common Sports Injuries for Special Physical Training - Tao Lei; Yi Huang; Zhijuan Zhou (Occupational Therapy International)
This paper provides an in-depth study of occupational therapy and the prevention of common sports injuries in special physical training. The issue of sports injuries and rehabilitation has always been a hot topic in special training. With the continuous development of sports, the increasing intensity of competition, and more stringent requirements for special techniques, the increase in difficulty and intensity of training has led to the increasing frequency of sports injuries, so how to prevent injuries in special physical training and rehabilitation and recovery of athletes after the injury is particularly important. Since the most common musculoskeletal injuries occur in the lower quadrant, this paper proposes a lower extremity functional test (LEFT) model as a means of identifying injury risk and guiding the implementation of training programs to prevent sports injuries. In this paper, a knee injury is used as an example, and an occupational therapy program of TCM physical therapy+aquatic rehabilitation is adopted for the already occurred sports injuries. Through interviews and clinical examinations of athletes, coaches, and medical personnel, this paper summarizes the sites, types, characteristics, and probability of occurrence of common sports injuries in special physical training. Experiments were conducted through clinical rehabilitation of common sports injuries with the addition of TCM manual massage. A series of effects of this modality on the rehabilitation of sports injuries were examined by monitoring physiological and biochemical indexes and by comparative analysis before and after testing physical function indexes using the Omega Wave system. Sports injuries are diverse. Traditional Chinese medicine physical therapy+water rehabilitation therapy is an effective physical therapy method. According to the relevant theories of traditional Chinese medicine treatment, diagnosis and treatment through meridians and related acupuncture points have significant curative effects. Traditional Chinese medicine, massage, and acupuncture have irreplaceable roles in the rehabilitation and treatment of sports injuries and can effectively improve and cure sports injuries.